2020
DOI: 10.3390/en14010013
|View full text |Cite
|
Sign up to set email alerts
|

Long Short-Term Memory Network-Based Normal Pattern Group for Fault Detection of Three-Shaft Marine Gas Turbine

Abstract: Fault detection and diagnosis can improve safety and reliability of gas turbines. Current studies on gas turbine fault detection and diagnosis mainly focus on the case of abundant fault samples. However, fault data are rare or even unavailable for gas turbines, especially newly-run gas turbines. Aiming to realize fault detection with only normal data, this paper proposes the concept of normal pattern group. A group of long-short term memory (LSTM) networks are first used for characterizing the mapping relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Recently, considerable reports have been presented on its application for system and rotating machinery health management [24,50] including gas turbine prognostics [51][52][53]. There were also a few attempts to employ LSTM for gas turbine diagnostics as well [54].…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…Recently, considerable reports have been presented on its application for system and rotating machinery health management [24,50] including gas turbine prognostics [51][52][53]. There were also a few attempts to employ LSTM for gas turbine diagnostics as well [54].…”
Section: Long Short-term Memorymentioning
confidence: 99%
“…In [23], an NN-based FD is proposed for hydraulic systems, and it is shown that using NNs improves the accuracy. A deep learned NN scheme is designed in [24] for the FD problem in gas turbines. In [25], an FLS is used to approximate the flow pattern, and then based on the FLS model, the flow is predicted, and an FD scheme is designed.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Remark 4. The results in Figures [23][24][25][26] show that the suggested FD scheme gives a good detection performance versus various faults. Furthermore, Table 2 shows a good robustness against disturbances that have been considered as external noises.…”
Section: Remarkmentioning
confidence: 99%
“…The authors stated that this approach outperformed the existing ones and that this method could be applied in time-sensitive scenarios. Similarly, in [82], a method to accomplish fault detection with only normal data introducing the concept of the normal pattern group was proposed. A group of LSTM machines was used to characterise the measurable healthy parameters of the gas turbines to later identify the gas path faults.…”
Section: Fault Detectionmentioning
confidence: 99%